(3GdQSGdI GdbTjQjI aj GdJUhas - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s ((3CMeO Hf YHO GdQMef Hf eMeO GdWHjb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HLdGd edchJg s
(3BNQgG (B:s
(3agPg hUjJfG Edi GdeQjOjf , fSCd Gddg GdcQje dge GdJhajb hdg GdMeO ddg Ydi eG jSQ , hgh MSHfG hfYe GdeYjf s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJ hJUMjMGJs
(3HBNQgG ebGHdI SfI (B794s
(3hcJHJ QDhS GdGHhGH HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
Keywords: (3GdJUha hGdBOGH GdTQYjIs